Loss of POMC-mediated antinociception contributes to painful diabetic neuropathy - Deshpande, Divija; Agarwal, Nitin; Fleming, Thomas; Gaveriaux-Ruff, Claire; Klose, Christoph S. N.; Tappe-Theodor, Anke; Kuner, Rohini; Nawroth, Peter Paul (Nature Communications, 2021)
Painful neuropathy is a frequent complication in diabetes. Proopiomelanocortin (POMC) is an endogenous opioid precursor peptide, which plays a protective role against pain. Here, we report dysfunctional POMC-mediated antinociception in sensory neurons in diabetes. In streptozotocin-induced diabetic mice the Pomc promoter is repressed due to increased binding of NF-kB p50 subunit, leading to a loss in basal POMC level in peripheral nerves. Decreased POMC levels are also observed in peripheral nervous system tissue from diabetic patients. The antinociceptive pathway mediated by POMC is further impaired due to lysosomal degradation of μ-opioid receptor (MOR). Importantly, the neuropathic phenotype of the diabetic mice is rescued upon viral overexpression of POMC and MOR in the sensory ganglia. This study identifies an antinociceptive mechanism in the sensory ganglia that paves a way for a potential therapy for diabetic neuropathic pain.
Gesehen am 03.03.2021